Yerevan Master Plan: Utopia or Reality? - Arustamyan, Arsen (Scientific Papers of National University of Architecture and Construction of Armenia, 2023)
The article deals with the urban problems of the city of Yerevan. Based on the analysis of the current state of urban planning science and on examples of foreign experience in the design and development of large cities, the issues of design and construction that ensure their sustainable development are considered. The question is raised about replacing the general plan of the city with the concept of city development for the short term of 5…7 years. This mainly concerns the design methodology and the transition from currently existing resource goals to social goals, which in modern conditions will make it possible to more productively, taking into account the available resources, predict the development of the city, will save significant territories and improve the quality of service.